2014
DOI: 10.7498/aps.63.170202
|View full text |Cite
|
Sign up to set email alerts
|

Noether symmetry and Mei symmetry of a discrete holonomic mechanical system with variable mass

Abstract: This paper studies the Noether symmetry and Mei symmetry of a discrete holonomic mechanical system with variable mass. Firstly, by the difference discrete variation approach, the discrete equations of motion of the system are established. Secondly, the definitions of Noether symmetry and Mei symmetry are given, and the conditions under which the Noether conserved quantity can be induced by Noether symmetry and Mei symmetry are obtained. Finally, an example is discussed to illustrate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Further, we found that borneol induced human primary glioma cell apoptosis with concentration dependence, but the effect was reversed after transfection of HIF-1 overexpression plasmid. Li Feifei [27] reported that borneol (Natural Borneol) can cause apoptosis of human nasopharyngeal carcinoma, squamous cell carcinoma, adenocarcinoma and breast cancer cells. Apoptosis is a cascade of active cell death process, which is regulated by many genes and closely related to Caspase-3 family and BCL-2 family.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we found that borneol induced human primary glioma cell apoptosis with concentration dependence, but the effect was reversed after transfection of HIF-1 overexpression plasmid. Li Feifei [27] reported that borneol (Natural Borneol) can cause apoptosis of human nasopharyngeal carcinoma, squamous cell carcinoma, adenocarcinoma and breast cancer cells. Apoptosis is a cascade of active cell death process, which is regulated by many genes and closely related to Caspase-3 family and BCL-2 family.…”
Section: Discussionmentioning
confidence: 99%